2022
DOI: 10.3390/molecules27134086
|View full text |Cite
|
Sign up to set email alerts
|

Connarus semidecandrus Jack Exerts Anti-Alopecia Effects by Targeting 5α-Reductase Activity and an Intrinsic Apoptotic Pathway

Abstract: There is a growing demand for hair loss treatments with minimal side effects and recurrence potential. Connarus semidecandrus Jack has been used as a folk medicine for fever in tropical regions, but its anti-alopecia effects remain unclear. In this study, the anti-androgenic alopecia effect of an ethanol extract of Connarus semidecandrus Jack (Cs-EE) was demonstrated in a testosterone-induced androgenic alopecia (AGA) model, in terms of the hair–skin ratio, hair type frequency, and hair thickness. The area of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The released cytochrome c combines with procaspase 9 and other complexes to form apoptosomes. These apoptosomes then activate the caspase-3 signalling cascade, thereby inducing cell destruction [37]. Studies have shown that the PI3K/Akt pathway may play a key role in apoptosis.…”
Section: Plos Onementioning
confidence: 99%
“…The released cytochrome c combines with procaspase 9 and other complexes to form apoptosomes. These apoptosomes then activate the caspase-3 signalling cascade, thereby inducing cell destruction [37]. Studies have shown that the PI3K/Akt pathway may play a key role in apoptosis.…”
Section: Plos Onementioning
confidence: 99%
“…Some of these papers were inspired by information on the use of plants in traditional medicine, such as the photoaging effect of Potentilla glabra [ 3 ], wound healing and melanogenic inhibitory effect of Angelica polymorpha flower [ 4 ], stretch mark inhibition effect of Lagerstroemia indica flowers [ 5 ], anti-hair loss effect of Ulmus davidiana and Connarus semidecandrus [ 6 , 7 ], anti-aging effect of Cirsium japonicum flowers [ 8 ], and whitening effect of Pouteria macrophylla fruit [ 9 ].…”
mentioning
confidence: 99%